2015
DOI: 10.1016/j.fgb.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for homoploid speciation in Phytophthora alni supports taxonomic reclassification in this species complex

Abstract: Alder decline has been a problem along European watercourses since the early 1990s. Hybridization was identified as the main cause of this emerging disease. Indeed, the causal agent, a soil-borne pathogen named Phytophthora alni subsp. alni (Paa) is the result of interspecific hybridization between two taxa, Phytophthora alni subsp. multiformis (Pam) and Phytophthora alni subsp. uniformis (Pau), initially identified as subspecies of Paa. The aim of this work was to characterize the ploidy level within the P. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 66 publications
1
66
0
Order By: Relevance
“…Adapting the species concept to include hybridization is a more general problem also, emphasized in cases of oomycotan fungal analogues (Husson et al 2015). Recently, Husson et al (2015) have described the hybridization between two subspecies with different ploidies and the appearance of a new hybrid subspecies.…”
Section: Pathogenic Fungus As a Selection Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Adapting the species concept to include hybridization is a more general problem also, emphasized in cases of oomycotan fungal analogues (Husson et al 2015). Recently, Husson et al (2015) have described the hybridization between two subspecies with different ploidies and the appearance of a new hybrid subspecies.…”
Section: Pathogenic Fungus As a Selection Factormentioning
confidence: 99%
“…Recently, Husson et al (2015) have described the hybridization between two subspecies with different ploidies and the appearance of a new hybrid subspecies. The authors found that the new hybrid DNA was equal to half the sum of the parental DNAs, but one parental genome was tetraploid while the second was diploid.…”
Section: Pathogenic Fungus As a Selection Factormentioning
confidence: 99%
“…Since the early 1990s, it has been endangered by the hybrid oomycete Phytophthora ×alni, leading to dieback in riparian ecosystems (Husson et al 2015). This pathogen is the result of interspecific hybridization between two taxa, P. uniformis and P. ×multiformis.…”
Section: Communicated By P Ingvarssonmentioning
confidence: 99%
“…Phytophthora uniformis and Phytophthora ϫmultiformis have been identified as the parents of P. ϫalni (15,16). Recent work coupling flow cytometry and quantification of allele copy number determined the exact ploidy levels of the three species of the complex (17). Accordingly, P. ϫalni was shown to be a triploid homoploid-type taxon that formed through the hybridization of a diploid taxon (P. uniformis) and a tetraploid taxon (P. ϫmultiformis) without chromosome doubling.…”
mentioning
confidence: 99%